The power of online communities - Addison, Chris; Lopes Ramos, Isaura (Technical Centre for Agricultural and Rural Cooperation, 2016)
Smallholder farmers need to absorb a huge amount of information that will directly impact their work. Communities of practice can strengthen their ability to influence agricultural research and policy and improve their farming practices.